Terminology - clarifying the current confusion and presenting the correct terminology - Ansari, Ejaz (Frontiers in Ophthalmology, 2023)
Most readers will be familiar with terminology (from meetings and conferences) that we, the editors, would deem to be incorrect or confusing. In general, we all tend to accept the information conveyed to us without really questioning what the terms truly mean. Therefore, the subsequent chapters discussing the IOLs in question should be studied with this in mind since a lot of familiar terminology will be used in those chapters, which, strictly speaking, may not be in line with the most accurate terminology and classification. The reader is encouraged to read this full article to be mindful of the current confusion surrounding IOL terminology and what the correct terminology should be. This is so that one is better prepared to understand and question the mechanism of action and side effects of IOLs that one is planning to use.